Decomposition and nutrient release of maize stover and groundnut haulm under tropical field conditions of Malaysia - Mubarak, A. R.; Rosenani, A. B.; Anuar, A. R.; Zauyah, S. (Taylor and Francis Group, 2002)
Recycling of crop residues is essential to integrated and sustainable agricultural management system. Thus, it is of crucial importance to study the decomposition of these residues particularly in the humid-tropics. A litterbag experiment was carried out on an acid soil of the humid tropics of Malaysia. Haulm from groundnut and stover from were placed inside nylon 2 mm mesh bags (20 cm × 20 cm) and placed on the soil surface in the field with a groundnut-maize rotation system. A total of 21 bags for maize and an equal number for groundnut residues were placed in a field plot. Three bags of each residue type were retrieved at 1, 3, 5, 7, 9, 11 and 13 weeks of decomposition. The decomposed tissue was analyzed for remaining dry matter weight (DMW), nitrogen (N), carbon (C), phosphorus (P), potassium (K), calcium (Ca), and magnesium (Mg) contents. Dry matter disappearance rate constant (0.158% week-1) from groundnut haulm was significantly (P = 0.01) faster than that from maize stover (0.099% week-1). A 50% loss of residue N was found after 2 weeks for maize residues and only 1.5 weeks for groundnut residues. Generally, nutrient loss from both residues was in the order of K ≥ P = N = Mg ≥ Ca. The results indicated that sowing time of subsequent crop after residue application is crucial to synchronize nutrient release with plant uptake.